PENERAPAN HABIT TRACKER UNTUK MENINGKATKAN LATIHAN MANDIRI PADA KOMUNITAS PADUAN SUARA GEREJA - Angela Nathania Kurniawan; Audi Karina Budiman; Hafsa Nur Rahayu Putri; Jessica Carissa Augustine Budi; Regina Sugito; Penny Handayani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2026)
Gita Crescentia is a Catholic youth community choir at St. Yakobus Church, Jakarta, which faces issues with the members’ low frequency of individual vocal practice. This problem affects the quality of rehearsals and overall performance during services. Through a community-based approach, a habit tracker intervention was designed and implemented over two weeks to encourage independent practice habits. The intervention involved active participation from members and committees of the community. It was evaluated formatively using Global Progress and summatively with Self Report Habit Index (SRHI). Results indicated an increase in the average frequency of independent practice from the first to the second week. These findings indicate that the habit trackers contributed to building a more consistent and autonomous rehearsal routine, the impact however was not significant. This activity highlights the importance of member participation in designing programs relevant to the community’s needs and the role of ongoing monitoring in sustaining newly formed habits.